(untitled) (Journal of Medicine, 2010)
Viral hepatitis is the inflammation of the liver caused by hepatitis viruses. The most common causes of viral hepatitis are the five unrelated hepatotropic viruses Hepatitis A, Hepatitis B, Hepatitis C, Hepatitis D, and Hepatitis E. The aim of this study is to assess the biochemical parameters in viral hepatitis which varies with respect to the different types of viral hepatitis. Sex of the patient affected by Hepatitis A was almost similar in male and female, being 9 (45%) and 11 (55%) in respectively. But in contrast, more than eighty per cent (85%) Hepatitis-E affected population was male. Similar scenario was found in Hepatitis B And C infection (Male- 75%,67%, Female 25,35%). Mean value with standard deviation (±SD) of serum bilirubin level was highest in Hepatitis E (251 ± 125.19 ìmol/l). Value of serum ALT in hepatitis E was found to be 1794 U/l (highest), hepatitis B 1362 U/l hepatitis C are 135.45 U/L,. Serum aspartate aminotransferase (S.AST) is also raised in all types of vira hepatitis but more in Hepatitis E (765 U/l) and Hepatitis B (430 U/l). Serum Alkaline Phosphatase (ALP) was raised significantly in Hepatitis B (240 U/l). The prothombin time was more altered in Hepatitis-E (22.7seconds) and Hepatitis-B (18.5 seconds). There was no significant alteration in serum protein level. So, it can be concluded that derangement of biochemical parameters in patients suffering from common types of viral hepatitis is more in HEV and HBV and comparatively less in HAV and HCV. Keywords: Viral hepatitis, hepatitis A, hepatitis B, hepatitis C, hepatitis D, hepatitis E DOI:10.3329/jom.v11i1.4268 J Medicine 2010: 11: 42-45